2019
DOI: 10.1002/ffo2.24
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of organizational vigilance: Leadership, foresight, and adaptation in three sectors

Abstract: Why are vigilant organizations better at developing foresight than their rivals and acting faster on the insights and alerts? Four attributes were hypothesized to explain the difference between vigilant and vulnerable organizations: (a) a leadership commitment to sensing and acting early on signals of change, (b) strategic investments in foresight abilities, (c) a flexible approach to incorporating uncertainty in their strategy processes, and (d) clear accountability and coordination for sharing information an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(28 reference statements)
0
13
0
1
Order By: Relevance
“…Such behavioral bounds are at the center of the skepticism about the ability of firms to adapt to changing environments (Gavetti et al, ). It gives rise to the hope that investment in CF practices can indeed help organizations become more adaptive to environmental changes, as suggested by Schoemaker and Day () and Vecchiato et al (). The findings also give support to the assumption that organizations may be able to proactively shape the future, as Hamel and Prahalad () called for already in 1994.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Such behavioral bounds are at the center of the skepticism about the ability of firms to adapt to changing environments (Gavetti et al, ). It gives rise to the hope that investment in CF practices can indeed help organizations become more adaptive to environmental changes, as suggested by Schoemaker and Day () and Vecchiato et al (). The findings also give support to the assumption that organizations may be able to proactively shape the future, as Hamel and Prahalad () called for already in 1994.…”
Section: Resultsmentioning
confidence: 97%
“…Anticipatory practices in firms, also referred to as corporate foresight (CF), are expected to contribute to a firm's ability to adopt new courses of action that are markedly different from the status quo and potentially capable of changing the game in entire industries (Gavetti & Menon, ; Rohrbeck & Kum, ). Investment in such practices has been shown to have a significant positive effect on the ability of a firm to see external changes sooner and act on them faster (Schoemaker & Day, ). It has also been argued that companies that adopt longer time horizons are, first, able to counteract managerial myopia and second, able to enhance value (Flammer & Bansal, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vigilant leadership manages an environment that is constantly changing in response to these changes through entrepreneurial marketing. Schoemaker and Day ( 2020 ) examined the determinants of organizational vigilance and found that vigilant leadership was the second strongest factor influencing organizational awareness after investing in environmental scanning. In line with this, vigilant leadership has consequences on organizational performance (Day and Schoemaker 2019 ) by integrating organizational networks in scenario planning through strategic radars that can detect weak signals from turbulent environments (Schoemaker et al 2013 ).…”
Section: The Moderating Role Of Vigilant Leadership On the Relationsh...mentioning
confidence: 99%
“…7 We then hypothesized that four main drivers of organizational vigilance would best distinguish vigilant from vulnerable organizations. These hypotheses were tested with a survey 8 of senior leaders of 118 companies from around the world (see Appendix A). The four drivers, 9 in order of their relative influence in our study, are:…”
Section: Distinguishing Vigilant From Vulnerable Organizationsmentioning
confidence: 99%